Methods and tools for the abstraction of object models in web content by end users - Tacuri, Alex (2022)
The main idea is to organize the data exposed in Web site interfaces so that they can be processed or used efficiently, either by a person or automated by a machine through an algorithm. The structure or model that will be used in this approach is that of a graph, where each node will be an object abstracted from the DOM. From the point of view of external structures, currently the information on the web is very little combinable, to be able to establish connections or think about object relationships, which leads to not being able to process information effectively and efficiently, In addition, automating a task becomes complex, so providing a user with a model in which they can integrate this data and information will greatly alleviate this lack of integration.